Smallest-space analysis vs. the method of principal components: Another look at Ahamad's analysis of crimes - Raveh, Adi (Journal of quantitative criminology, 1986)
This paper presents a reanalysis of the Ahamad case study of 18 types of offenses. The suggested method is a nonmetric multidimensional scaling type called smallest-space analysis (SSA-I) which uncovers findings that were not expressed explicitly by the principal-components method used by Ahamad.